Analisis Literatur tentang Intervensi Psikologis Berbasis Mindfulness dan Dukungan Sosial terhadap Stres Akademik Mahasiswa - Irma Julita; Firman Firman; Netrawati Netrawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Academic stress is a common challenge experienced by students due to the burden and pressure in higher education environments. This study conducted a systematic literature analysis to evaluate the effectiveness of mindfulness-based psychological interventions and social support in addressing academic stress. By reviewing various empirical studies from leading journals, it was found that mindfulness—through techniques such as Mindfulness-Based Stress Reduction (MBSR)—is beneficial in reducing stress, anxiety, and improving students' emotional regulation and learning focus. In addition, social support from family, friends, and the campus environment acts as a stress buffer by providing emotional support and a sense of connectedness. An approach that combines mindfulness and social support has shown more effective results in helping students manage academic stress. Therefore, it is recommended that higher education institutions develop programs that integrate these two interventions to improve students' mental well-being sustainably.